A STUDY OF THE IMPACT OF FAMILY ENVIRONMENT ON THE ACADEMIC INTEREST OF HIGH SCHOOL STUDENTS - Shukla, Beena; Shroff, Sangeeta (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Education is very important for the development and prosperity of any nation. After education was included in the fundamental rights in India, today there are lakhs of children who are unable to go to school or leave going to school at the primary level itself and some children also start working at the age of playing and studying due to poverty of the family, financial crisis, separation from family due to natural disaster and lack of social security. Without education, a person cannot develop completely. Education is the most important part of human life. The environment of everyone’s family affects the mental health of children. Like a school, the family also has a special place in the psychological development of a child. The family plays an important role in the development of the personality of the child. Usually, the sanskar of virtues and vices in the child is instilled in the family environment itself. The background of the family plays an important role in the development of a child.